Synergies Between Coastal Management and Coal Mining: Approaches to Support a Sustainable Economy - Abdunnur, Abdunnur; Mayulu, Hamdi (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2025)
Coastal and marine areas have ecological and economic potential for development and utilization across multiple sectors, including mining. However, the interaction between coastal management and coal mining operations often leads to adverse ecological consequences and socio-environmental conflicts that threaten sustainability. To address these challenges, integrated approaches are required to promote synergy between coastal management and coal mining practices. This review adopts an exploratory approach through comprehensive literature analysis, with data drawn from reputable scientific databases, including Scopus, Web of Science, MDPI, and PubMed. The selected studies were systematically identified and analyzed using qualitative descriptive techniques. Achieving sustainable management in both coastal and coal mining sectors requires a holistic perspective that incorporates sociocultural, economic, environmental, and governance dimensions. Environmentally friendly technologies, rehabilitation of degraded coastal and post-mining ecosystems, and empowerment of local communities are among the alternative strategies that can be implemented to align both sectors toward shared economic goals. Economic benefits can be enhanced by optimizing the collaborative potential of the coastal and coal mining sectors, particularly through the establishment of green employment opportunities, the development of ecotourism, and the sustainable utilization of natural resources. The realization of sustainable coastal and coal mining management relies on synergistic cooperation among mining companies, governmental bodies, academia, stakeholders, and local communities to promote a sustainable economy